Features of the exchange of electrolytes and nitrogenous metabolites under different options of uric acid exchange in healthy female rats - Bombushkar, Igor; Gozhenko, Anatoliy; Korda, Inna; Badiuk, Nataliya; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2020)
Background. We previously identified 4 variants-clusters of uricemia and uricosuria both in rats and in humans. It was shown that the clusters differ from each other in the constellation of immune, autonomic and endocrine parameters, which correlate with uricemia and uricosuria. The aim of this study was to identify the electrolytes and nitrogenous metabolites, the combination of which differentiates previously formed quantitative and qualitative variants of uric acid metabolism in rats. Materials and Methods. Experiment was performed on 60 healthy female Wistar rats 220-300 g. The plasma and urine levels of the uric acid, urea, creatinine, calcium, phosphates, chloride, magnesium, sodium and potassium (also in erythrocytes) as well as glucose (in plasma only) were determined. Results. 10 metabolic parameters characteristic of four variants of uric acid exchange were identified: the concentration of glucose, urea, phosphates, magnesium and potassium in plasma, and the latter in erythrocytes, as well as the excretion of creatinine, urea, phosphates and calcium with urine. The accuracy of discrimination of clusters based on the totality of this metabolic constellation together with uricemia is 95%. The cumulative determining influence of the parameters of uric acid exchange (due to the significant advantage of uricosuria over uricemia) on the constellation of metabolic parameters is 56%. Diuresis and excretion of phosphates and potassium are subject to the maximum positive determination from the side of uric acid; excretion of calcium, creatinine and urea are determined to a lesser extent; levels of creatinine, urea and potassium in the plasma are even less, and magnesiumuria is subject to the minimum determination. Conclusion. Uric acid is naturally associated with the state of electrolytes and nitrogenous metabolites exchange in healthy female rats.